2015
DOI: 10.1002/stem.2067
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Proteomic Profiling of Extra-Embryonic Endoderm Differentiation in Mouse Embryonic Stem Cells

Abstract: During mammalian preimplantation development, the cells of the blastocyst's inner cell mass differentiate into the epiblast and primitive endoderm lineages, which give rise to the fetus and extra-embryonic tissues, respectively. Extra-embryonic endoderm (XEN) differentiation can be modeled in vitro by induced expression of GATA transcription factors in mouse embryonic stem cells. Here, we use this GATA-inducible system to quantitatively monitor the dynamics of global proteomic changes during the early stages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 54 publications
5
14
0
Order By: Relevance
“…Consistent with previous studies (Fujikura et al, 2002;Mulvey et al, 2015;Shimosato et al, 2007), we found that transient expression of doxycycline-inducible GATA4-FLAG instead of GATA6-FLAG led to the same expression pattern of endogenous GATA factors, but doubled the proportion of differentiating cells ( Fig. 1 D -F, supplementary material Fig.…”
Section: Fig 1: Expression Of Endogenous Markers Of Pre-like Differesupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies (Fujikura et al, 2002;Mulvey et al, 2015;Shimosato et al, 2007), we found that transient expression of doxycycline-inducible GATA4-FLAG instead of GATA6-FLAG led to the same expression pattern of endogenous GATA factors, but doubled the proportion of differentiating cells ( Fig. 1 D -F, supplementary material Fig.…”
Section: Fig 1: Expression Of Endogenous Markers Of Pre-like Differesupporting
confidence: 92%
“…To model in culture the transition from Nanog;GATA6 co-expression to mutually exclusive expression of Epi and PrE markers that characterizes the Epi-versus-PrE fate decision (Plusa et al, 2008), we used a doxycycline-inducible system to transiently express GATA6-FLAG in ES cells (Beard et al, 2006;Mulvey et al, 2015;Wamaitha et al, 2015) (Fig. 1A).…”
Section: An Es-cell Model System To Investigate Pre-like Fate Choice mentioning
confidence: 99%
“…1b). Moreover, the XEN-like cells measured here were similar to embryo derived XEN cells in their proteome (Mulvey et al, 2015) (r = 0.65, Supplementary Fig. 1c).…”
Section: Measurement Of Transcriptome and Proteome Dynamics During Resupporting
confidence: 66%
“…4b). This might be related to the fact that XEN cells have to produce high levels of extracellular matrix proteins (Mulvey et al, 2015), like laminin (Lamb1) or collagen (Col4a2) . Consequently, these proteins must be synthesized in a timely manner to ensure the proper function of the XEN cells.…”
Section: Sets Of Genes With Different Functions In Differentiation Shmentioning
confidence: 99%
See 1 more Smart Citation